A sled push stimulus potentiates subsequent 20-m sprint performance - Seitz, L. B.; Mina, M. A.; Haff, G. G. (Journal of Science and Medicine in Sport, 2017)
Objectives: The objective of this study was to examine the potentiating effects of performing a single sprint-style sled push on subsequent unresisted 20 m sprint performance. Design: Randomized crossover design. Methods: Following a familiarization session, twenty rugby league players performed maximal unresisted 20 m sprints before and 15 s, 4, 8 and 12 min after a single sled push stimulus loaded with either 75 or 125% body mass. The two sled push conditions were performed in a randomized order over a one-week period. The fastest sprint time recorded before each sled push was compared to that recorded at each time point after to determine the post-activation potentiation (PAP) effect. Results: After the 75% body mass sled push, sprint time was 0.26 ± 1.03% slower at the 15 s time point (effect size [ES] = 0.07) but faster at the 4 (-0.95 ± 2.00%; ES = -0.22), 8 (-1.80 ± 1.43%; ES = -0.42) and 12 (-1.54 ± 1.54%; ES = -0.36) min time points. Sprint time was slower at all the time points after the 125% body mass sled (1.36 ± 2.36%-2.59 ± 2.90%; ESs = 0.34-0.64). Conclusions: Twenty-meter sprint performance is potentiated 4-12 min following a sled push loaded with 75% body mass while it is impaired after a 125% body mass sled. These results are of great importance for coaches seeking to potentiate sprint performance with the sled push exercise.